EVALUASI PROGRAM TAHSIN/TAHFIDZ QUR’AN DI SDIT AZ-ZAHRAH GOWA MENGGUNAKAN MODEL CIPP - Sulkifli, Sulkifli; Humairah, Humairah; Sarkiah, Sitti; Khumairah, Eka Silfiah; Amir, Zulfhaa (STKIP Pesisir Selatan, 2025)
Evaluation of educational programs is a step towards achieving the goals of Islamic education. As Muslims, it is important to carry out the religious orders contained in the Qur'an. The Qur'an, as a guide and reference for Muslims, applies not only when the verse was revealed, but also until the end of time. This research uses a qualitative approach with an evaluative study method that applies the CIPP (Context, Input, Process, Product) model. The evaluation results show that the implementation of the tahsin/tahfidz program at SDIT Az-zahrah meets the context evaluation criteria in accordance with school needs. Input evaluation showed that overall, the program received a good category, with an assessment of human resources, facilities and infrastructure, funds, and procedures used. The process evaluation of the program implementation showed good results, by identifying obstacles in the implementation, assessment process, and supervision. Meanwhile, the output evaluation of the program showed an overall excellent category, focusing on outputs, program outcomes, and benefits obtained by students. This evaluation provides in-depth feedback to program managers to continue to improve the effectiveness and efficiency of the implementation of the tahsin/tahfidz Al-Qur'an program at SDIT Az-zahrah.